2022
DOI: 10.3389/fendo.2022.915937
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and identification of an animal model of long-term exercise-induced fatigue

Abstract: In competitive sports, the training load is close to the human physiological limit, which will inevitably lead to exercise-induced fatigue. If fatigue cannot be recovered in time, it will eventually lead to excessive training and affect sport performance. Therefore, fatigue has become an important part of the physical function assessment for athletes. This paper will review animal models of long-term exercise-induced fatigue, modeling schemes of mice under treadmill and swimming training, phenotypes of long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…However, the results of the present study were inconsistent with those of previous studies. The blood biomarkers used in this study have been reported to increase during or immediately after exercise [ 4 ]. In the present study, blood samples were taken 2 days after the treadmill fatigue test was performed, which may not have reflected the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the present study were inconsistent with those of previous studies. The blood biomarkers used in this study have been reported to increase during or immediately after exercise [ 4 ]. In the present study, blood samples were taken 2 days after the treadmill fatigue test was performed, which may not have reflected the results.…”
Section: Discussionmentioning
confidence: 99%
“…And more, muscle function is closely linked to exercise-induced fatigue. Exercise-induced fatigue influences efficiency of operations and leads to inability of muscles 15 . However, the treatment effect of EA on fatigue was not uncovered because of its sophisticated pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The average water area was 320 cm 2 per rat, the depth of water was 50 cm, and the water temperature was 34 ± 2 • C. The rats were removed from the water immediately after swimming to exhaustion, and the exhaustion time was recorded. The exhaustion was judged according to the criteria in the literature [15,16].…”
Section: Exhaustive Forced Swimming Testmentioning
confidence: 99%